Impact of Government Expenditure and Value Added Tax on Nigerian Economy - Babalola , Oladapo O. (Àgídìgbo: ABUAD Journal of the Humanities, 2014)
This work examines the impact of Government expenditure and Value Added Tax (VAT) on economic growth. The standard Ordinary Least Square (OLS) was used to test the explanatory variable on the dependent variable, using data sourced from the Central Bank of Nigeria (CBN) Annual Bulletin and National Bureau Statistics (NBS), with scope covering 1994-2011. Results showed a positive relationship between VAT and GDP (Economic Growth), but negative for government expenditure, due to government engaging in consumption expenditure rather than capital expenditure. Though VAT adoption is a major landmark for our ailing economy, the side effects needs to be well managed to increase aggregate welfare effect on citizens and the economy. However, the penalty for evading the payment must not be relaxed while government ensures the location of VAT offices close to the rural centres so that VATabie people can be accessed.